St. Helena: An Important Reproductive Habitat for Whale Sharks (Rhincodon typus) in the Central South Atlantic - Perry, Cameron T.; Clingham, Elizabeth; Webb, D. Harry; de la Parra, Rafael; Pierce, Simon J.; Beard, Annalea; Henry, LeeAnn; Taylor, Beth; Andrews, Kenickie; Hobbs, Rhys; Araujo, Gonzalo; Dove, Alistair D. M. (Frontiers in Marine Science, 2020)
A reliable aggregation of whale sharks (Rhincodon typus) takes place in waters surrounding the remote South Atlantic island of St. Helena from December to May each year, peaking in January. A total of 277 individual sharks were identified over the course of the study, consisting of a 1.1:1 sex ratio of mature male and female sharks estimated to be between 5-12 m in total length. The SOCPROG best fit models estimated ~102 individual whale sharks at any one time with a decline to complete absence at ~75 days and an interannual periodicity for some sharks returning each season. Eyewitness accounts of mating behavior have been reported by reliable local observers on two separate occasions, which comprise the first observations of copulation in this species and are consistent with the size and sex demographics of the population. Horizontal movements away from the island proved difficult to track, due to extraordinarily deep-diving behavior that either damaged or caused premature detachment of the archival satellite tags, however, some individuals showed large scale movement away from the island towards both Africa and South America. Acoustic telemetry showed that animals use the habitats around the entire island, but are focused on the leeward side, particularly from James Bay to Barn Cap. Due to its likely role in the reproductive ecology of the whale shark, St. Helena represents a critical habitat for this endangered species and deserves concerted research efforts.